Tendências de publicação em 22 anos de Journal of Applied Behavior Analysis: uma atualização de Northup, Vollmer e Serrett (1993) - Silva, Anderson Ribeiro da (2016)
The purpose of this study was to identify and analyze publication trends of behavior analysts in the last 22 years of publication of Journal of Applied Behavior Analysis, between 1993 and 2015. This study update Northup, Vollmer and Serrett (1993). A sample of 314 articles were selected from a population of 1.704 articles published between 1993 and 2015. This sample was revised and categorized, and publication trends analyzed based on variables and categories defined by Northup et al. (1993). The analyze variable were: (1) type of article, (2) participants, (3) setting, (4) behavioral change agents, (5) target behavior, (6) use of behavioral procedures and (7) generalization and follow-up measures. The results indicated that the JABA remains one of research papers communication newspaper with few studies for review, discussion and methodological studies. The typical behavioral change agent identified in the analyzed research is the own experimenter. Most surveys are interventions with people with developmental disabilities. Positive reinforcement, verbal instruction and punishment are the most common procedures in the analyzed articles and research published still lack data on follow-up and generalization measures. Implications for future research on interventions by applied behavior analysts discussed based on the founded results